2017
DOI: 10.1152/ajpgi.00130.2017
|View full text |Cite
|
Sign up to set email alerts
|

Functional morphology of the lower esophageal sphincter and crural diaphragm determined by three-dimensional high-resolution esophago-gastric junction pressure profile and CT imaging

Abstract: The smooth muscles of the lower esophageal sphincter (LES) and skeletal muscles of the crural diaphragm (CD) provide a closure/antireflux barrier mechanism at the esophago-gastric junction (EGJ). A number of questions in regard to the pressure profile of the LES and CD remain unclear, e.g., ) Why is the LES pressure profile circumferentially asymmetric,) Is the crural diaphragm (CD) contraction also circumferentially asymmetric, and ) Where is the LES and CD pressure profile located in the anatomy of the esoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 28 publications
0
27
0
1
Order By: Relevance
“…Mittal et al evaluated the functional morphology of the GEJ using both computed tomography (CT) and threedimensional-high resolution manometry (3-D-HRM). 12 They were able to differentiate the contraction of the crural diaphragm (CD) from the intrinsic lower esophageal sphincter muscle by measuring pressure in the lower esophagus during the respiratory cycle while validating the location of the probe under CT. The end-expiratory GEJ pressure reflected the LES pressure alone and the increase in pressure with tidal and forced inspirations accounted for the contribution of the CD.…”
Section: Discussionmentioning
confidence: 99%
“…Mittal et al evaluated the functional morphology of the GEJ using both computed tomography (CT) and threedimensional-high resolution manometry (3-D-HRM). 12 They were able to differentiate the contraction of the crural diaphragm (CD) from the intrinsic lower esophageal sphincter muscle by measuring pressure in the lower esophagus during the respiratory cycle while validating the location of the probe under CT. The end-expiratory GEJ pressure reflected the LES pressure alone and the increase in pressure with tidal and forced inspirations accounted for the contribution of the CD.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in high‐resolution, 3D manometry have led to a detailed understanding of the pressure profile in this region. A recent study characterized the pressures averaged across 10 healthy adult patients (Mittal et al, 2017). Similar to other studies, they found that the profiles at the GEJHPZ were not symmetric.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Right‐most set shows forced inspiration (FI), note change in color scale bar. Reproduced and adapted with permission from Mittal R.K. et al (2017). Functional morphology of the lower esophageal sphincter and crural diaphragm determined by 3D high‐resolution esophagogastric junction pressure profile and CT imaging , American Journal of Physiology ‐ Gastrointestinal and Liver Physiology , 313(3): G212‐G219.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The CD consists of the right and left crus, and the right crus consists of left and right arms, which wrap around the distal esophagus. 39 The esophagus is also angulated to the left just cephalad to where it joins the stomach, forming the angle of His. 39 The intraluminal extension of the angle of His creates an anatomic structure known as the gastroesophageal flap valve, which is graded at retroflexion during upper endoscopy.…”
Section: Achalasia Achalasia Was First Described By Sir Thomas Willimentioning
confidence: 99%